Toward effective interventions to reduce diabetes distress among adults with type 1 diabetes: Enhancing Emotion regulation and cognitive skills. Issue 8 (August 2019) - Fisher, Lawrence; Hessler, Danielle; Polonsky, William; Strycker, Lisa; Bowyer, Vicky; Masharani, Umesh
Highlights: Interventions to reduce distress should target emotion regulation and cognition. Improvements in emotion regulation and cognitive skills occur together. Improvements in different domains of diabetes distress occur together. These findings provide a template for developing effective interventions. Abstract: Objective: We tested three models to determine how improvements in emotion regulation (ER) and cognitive skills (CS) as a result of intervention operate to affect reductions in diabetes distress DD. Methods: Change data were drawn from the baseline and 9-month T1-REDEEM trial. Adults with type 1 diabetes were recruited from several U.S. states and Toronto, Canada. A primary and two alternative structural equation models were tested to explore the directionality of effect: primary model – changes in ER and CS drive changes in DD; reverse model – changes in DD drive changes in ER and CS; and bidirectional model – changes in ER, CS and DD occur together with no directionality. Results: All three models displayed a good fit to the data. The primary model indicated 7 significant directional pathways: improvements in ER and CS operate together to drive reductions in DD. The reverse model only indicated that reductions in DD affected changes in one CS variable; and the bidirectional model indicated only that these results were bidirectional. Reductions in all tested domains of DD occurred together. Conclusions: Improvements in ER and CS drive reductions in DD. Practice implications: Interventions to reduce high DD should focus on improving ER and CS.